An empire on the edge : how Britain came to fight America - Bunker, Nick (New York : Alfred A. Knopf, 2014)
A British-perspective chronicle of the Boston Tea Party and other events that led up to the American Revolution traces three years of volatile politics, personalities and economics on both sides of the conflict.
Drawing on careful study of primary sources from Britain and the United States, this new account of the Boston Tea Party and the origins of the American Revolution shows how a lethal blend of politics, personalities, and economics led to a war that few welcomed but nobody could prevent. British author Nick Bunker tells the story of the last three years of mutual embitterment that preceded the outbreak of America's war for independence, also shedding new light on the roles of such familiar characters as Benjamin Franklin, John Hancock, and Thomas Hutchinson. It was a tragedy of errors, in which both sides shared responsibility: the British and the colonists failed to see how swiftly they were drifting toward violence until the process had gone beyond the point of no return. By the early 1770s, Great Britain had become addicted to financial speculation, led by a political elite increasingly baffled by a changing world. When the East India Company came close to collapse, it patched together a rescue plan whose disastrous side effect was the destruction of some tea. With lawyers in London calling the Tea Party treason, the British opted for punitive reprisals without foreseeing the resistance they would arouse, while Americans underestimated Britain's determination not to give way. By the summer of 1774, the descent into war had become irreversible.--From publisher description.
Prologue. The finest country in the world -- The old régime -- Pt. 1. The empire of speculation. The tiger's mouth -- "This dark affair": the Gaspée incident -- A bankrupt age -- The unhappiness of Lord North -- Ignorance and bad policy -- Pt. 2. The sending of the tea. The East India crisis -- Whigs, West Indians and Thomas Hutchinson -- Massachusetts on the eve -- The Boston Tea Party: prelude -- The Boston Tea Party: climax -- Pt. 3. Down the slope. The cabinet in winter -- "Boston must be destroyed" -- The revolution begins -- An election in Arcadia -- The arming of America -- The fatal dispatch -- Epilogue. The noble dead.
Includes bibliographical references and index.
Keywords: United States -- History -- Revolution, 1775-1783 -- Causes; United States -- History -- Colonial period, ca. 1600-1775.; United States -- Foreign relations -- Great Britain; Great Britain -- Foreign relations -- United States; Boston Tea Party, Boston, Mass., 1773.; Great Britain; United States; 1600 - 1783